Effect of a Pre-Treatment with Hydrochloric Acid on the Copper Solubilization of a Bornite Concentrate with Posterior Leaching in Chloride Medium [Efecto de Un Pre-Tratamiento Con Ácido Clorhídrico en la Solubilización de Cobre Desde Un Concentrado de Bornita Con Posterior Lixiviación en Medio Clorurado] - Navarro-Donoso, P; Vargas-Riquelme, C; Avila-Munoz, M; Duran-Robledo, C (Universidad Nacional de Colombia, 2022)
The formation of soluble species from a bornite flotation concentrate pre-treated with hydrochloric acid was studied. Copper recovery after a leaching in a H2SO4-NaCl solution was determined. The influence of acid concentration and ore particle size were evaluated. Chemical and morphological characterization of the samples before and after the leaching were carried out by XRD and SEM to evaluate changes in the bornite. It was revealed that increasing acid concentration during the pre-treatment dramatically enhances the formation of soluble species, reaching in one case 49.0% of copper dissolution after 15 d of pretreatment and 24 h of leaching, both at 25 °C, without reducing the particle size of the concentrate. It was also revealed that the ore particle size did not affect the transformation rate into soluble species, due to the corrosive effect of HCl, which fractured and generated micro-pores on the surface of the particles studied. © The author; licensee Universidad Nacional de Colombia.